Seaweeds of the Greek coasts. I. Phaeophyceae - TSIAMIS, K.; PANAYOTIDIS, P.; ECONOMOU-AMILLI, A.; KATSAROS, C. (Mediterranean Marine Science, 2013)
An updated checklist of the brown seaweeds (Phaeophyceae) of Greece is provided, based on both literature records and new collections. The total number of species and infraspecific taxa currently accepted is 107. The occurrence of each taxon in the North Aegean, South Aegean and Ionian Seas is given. In addition, 17 taxa pending confirmation of their presence, 11 excludenda and 8 inquirenda are briefly discussed.